STRATEGI EKONOMI RUMAH TANGGA SOPIR ANGKUTAN UMUM OPLET (Studi Kasus Trayek Ramayana - Kulim) - Syahli, Zilman; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Oplet driver is an informal sector profession in the field of transportation services which is currently experiencing a decline in interest so that the income of oplet drivers is currently decreasing drastically. Oplet driver income is small and uncertain every day causing them to experience economic problems, especially in meeting the needs of family life. The purpose of this study was "to analyze the economic conditions of oplet driver households on the ramayana-kulim route" and "to analyze the way in which oplet drivers meet their family's living needs". The method used in this research is descriptive qualitative research method, in discuss This research is presented and analyzed in the form of descriptive (descriptive) words with a qualitative approach. In addition, this research is also supported by conducting in-depth interviews with informants (informants) that have been determined by researchers in advance. Here the writer takes the location of the research in Kelurahan Kulim, Pekanbaru City, especially the oplets on the ramayana-kulim route. Based on the results of the study, the current economic condition of the oplet driver's family. These are, on average, very deficient for food needs, they have to downsize so they are accustomed to being in debt. The impact of fierce competition in the world of public transport in urban areas, especially in the city of Pekanbaru resulted in a decline in the income of oplet drivers ass well as household economic problem. Therefore, the oplet drivers family adopts a survival strategy. There are three strategies by oplet drivers to be able to meet the needs of family life, namely active strategy, passive strategy and network strategy.Â Â Keywords: Survival Strategy, Oplet DriverÂ